LAND USE MODEL FOR BUILDING BASED ON CARRYING CAPACITY OF CITY LAND (CASE STUDY: PALU CITY) - Amar amar (Indonesian Journal of Geography, 2012)
This study aims to model the growth trend of the extent of land use for building based on thecarrying capacity of land in Palu city which is known as Bay City in accordance with theprediction of time. Methods of research were carried out with the approach of spatial andquantitative methods. The results show that Palu city as Bay City has the characteristics ofurban land that is quite specific to the protected area. There is still available land forbuilding i.e.: ± 13.151,13 ha (34.74%) with a growth rate of land use for building in thefuture 2.72% per year, area of cultivation will be fully filled in the year 2056 with thecapacity of 1.052.730 people. Carrying capacity of land in Palu city until the year 2056 hasnot exceeded the threshold, either by the land consumption per capita or by the level density.